Egan's Irish Whiskey: a story of heritage and renewal. Issue 2 (16th August 2021) - Du Plessis, Wendy; Peters, Mark
Abstract : Learning outcomes: The learning outcomes of this paper is as follows: to give faculty the opportunity to illustrate the strategist's and marketer's toolbox, namely, tools and frameworks such as the McKinsey 7S model. Porter's generic marketing strategies. Strengths, weaknesses, opportunities and threats analysis. Political, economic, social and cultural, technological, environment and legal – external macro analysis. The case is intended for use in MBA and Executive education courses in strategy, marketing and leadership. The case offers relevant experiences and instructive lessons in formulating and implementing business strategies. The case highlights the importance of contextual leadership intelligence and competence in enabling entrepreneurial business activities. The case gives students the opportunity to apply a strategic framework to marketing communications, competitive analysis and branding with a new brand and a new name in a first world economy. The case helps students understand that: successful companies are a success because of their people and leadership, proactive thinking and constantly looking for new opportunities will make you a leader in the market, up-to-date competitor and market analysis are paramount in making the winning decision, staying true to one's business philosophy and company values build a reputable organization, the importance of creating partnerships and healthy relationships with the distribution channel, the concept of competitive advantage, the concept of differentiation, focus and cost leadership and the concept of value and understanding customer needs. Case overview/synopsis: The Egan's Whiskey case offers students a unique opportunity to discover the important, yet grass-root, strategic decisions made by a high-quality alcohol product in a very competitive, well-known brand dominated the market, the USA. The case focuses specifically on issues related to strategic choices and implementation, brand, reputation, leadership, strategic marketing decision-making, customer/retail relationships, customer value and the importance of good marketing intelligence. There are some good examples of out-of-the-box thinking. History reveals that companies with the strongest brands, most proactive leadership, innovative marketing ideas, superb marketing intelligence and deepest relationships with their consumers are the pillars of success. The very assets that define these leading companies provide benchmarks for upcoming organizations. Being complacent and having poor leadership and vision in an ever-demanding customer-driven and competitive environment is a recipe for failure. Organizations and their leadership teams need to start thinking systematically, proactively and strategically about their place in competitive markets and take quick actions to mitigate risks and miss opportunities before they become reality. This case reveals the importance of understanding your strategic landscape, your market, your competitors, your customers, quick thinking and actions and having a rolling strategic plan, which is adaptable. Complexity academic level: The case is intended for use in MBA and Executive education courses in strategy, marketing and leadership. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 11: Strategy.